Фізико-хімічний аналіз комплексного відновлення Cr2FeO4 за участю метану - Гришин, О.М.; Надточій, А.А.; Петренко, В.О. (Physico-technological Institute of Metals and Alloys, 2023)
The paper presents the results of a thermodynamic analysis of the complex reduction of iron chromite with the participation of methane at temperatures precluding the charge melting. Some possible physicochemical recovery models are considered. The process of iron chromite reduction by methane without disproportionation is more likely thermodynamically (at T above 800 K). Reduction of chromite with mixtures (CH4 + CO2) and (CH4 + H2O) contributes to the development of the conversion of CH4 in the presence of a catalytic surface, which can be Femet. It was concluded that the thermodynamic preference is given to methane conversion reactions at temperatures above ~ 953 K, that is, in the reduction of iron chromite. According to the proposed method, the temperature of the onset of the reduction of Cr2FeO4 by methane was calculated at the first and second stages of the reduction. The equilibrium composition of the gas phase is calculated for the reduction of chromite by methane in the case of inconstancy of the ratio of carbon and hydrogen containing gases (parameter n). Parameter n is influenced by two opposite processes – by carbon gasification reaction, which leads to a decrease in parameter n, and methane decomposition, which increases the content of hydrogen-containing gases. A method is proposed and the parameter n is calculated to reduce iron chromite by methane, according to the data obtained, the temperature dependences of the parameter n were constructed for the first and second stages of chromite reduction under the condition of the stoichiometric ratio (C + H2)/O. With carbon deficiency, a more complex scheme is used, which is characterized by varying degrees of process completion depending on the C/O ratio. Thermodynamic modeling of the Cr-Fe-C-O-H system was performed for the variants of reducing chromite of iron with methane mixtures with water vapor and carbon dioxide. It is shown that the equilibrium gas phase at T > 1173K has a high reduction potential, which makes it possible to use the exhaust gas in the process. A fundamentally possible scheme of organization of the process using non-converted natural gas has been confirmed.